[PP.04.13] CALCIUM CT SCAN IN HYPERTENSIVE PATIENTS. (September 2017) - Vintila, A.; Tudorica, C.; Bulei, C.; Vintila, V.
Abstract : Objective: Coronary atherosclerosis is a common finding in hypertensive patients. It may be symptomatic or not. Evaluation by coronary angiography is used in clinical settings thoroughly selected due to invasiveness and potential complications. We aimed at investigating coronary CT findings in hypertensive patients with or without clinical diagnosis of coronary artery disease. Design and method: We studied a group of 26 hypertensive patients, aged 62 +/− 14 years, in whom coronary CT has been ordered for clinical purposes. Patients were evaluated according to standards of care, including blood tests, resting ECG and transthoracic echocardiography. Data were collected and analysed using SPSS 19.0. Results: Ischemic heart disease was present in 18 patients: 1 with ECG changes but no symptoms, 7 with stable angina pectoris, 3 with antecedent myocardial infarction, 4 with coronary artery bypass grafting and 3 with percutaneous revascularisation. Coronary CT calcium score ranged from 0 to 3292. It was correlated with age (r = 0.548, p = 0.006), presence of ischemic heart disease (r = 0.740, p < 0.001) and hypertriglyceridemia (p = 0.578, p = 0.004). It was significantly higher in patients with conduction disturbances on resting ECG (average values 1185 versus 257, p = 0.027). We didn't find a correlation between coronary calcium score and number of coronary atherosclerotic lesions (p = 0.35). Conclusions: Coronary calcium score is a surrogate for coronary heart disease but it is not a reliable marker to identify the number, type and severity of atherosclerotic lesions.